Linguistic tools for embodied minds - Anna M. Borghi; Felice Cimatti; Marco Tullio Liuzza (Rivista Italiana di Filosofia del Linguaggio)
In this paper, we outline the embodied perspective of language comprehension indicating some of its limitations. We claim that the notions of language as a tool (CLARK 2006a, 2006b), might be useful to overcome a view focused only on referential aspects of language. Words, in quality of tools, can: a. facilitate communication among speakers; b. influence categorization; c. have a different impact on concrete and abstract words; d. allow us to construct an inner speech. Finally, we discuss how thinking about language as tool can help inform future research on thought, language and body